Lambda Nachrichten : Zeitschrift der Homosexuellen Initiative Wien (Wien: HOSI)
"Fonds Suzan Daniel (FSD)Periodiciteit : driemaandelijksRedactie : Pf 22, 1037 Wien ; vanaf (1982) 3 : Novaragasse 40, 1020 Wien"